PENDIDIKAN KARAKTER POLA TAMANSISWA DI YOGYAKARTA - Kurniawan, Putut Wisnu (LPPM STKIP PGRI Bandar Lampung, 2014)
This study was conducted at Park High School Associate mother Pawiyatan in Yogyakarta. This is a form of qualitative descriptive research. Footage used in this study is purposive sampling with criterion-based selection. Data collection was carried out by direct observation, in-depth interviews, and recording documents. Data validation is done by triangulation. The analysis used is interactive model, namely data collection, data reduction, data display, and conclusion.The results of this study concluded that the pattern of application of character education in high school Taman Madya Mother Pawiyatan Yogyakarta is through learning curriculum (there are lessons that teach morals or manners), extracurricular activities, school culture, and exemplary teachers. Another pattern that is applied in Madya Park High School Mother is a system Pawiyatan Among the methods of educating the spirit of kinship which jointed to the independence and the nature of nature. The system was implemented to give students freedom to develop according to his ability with a family approach. Perceptions of teachers and students about character education will affect the implementation in schools. Perceptions of teachers and students about character education that appeared in the high school Taman Madya Mother Pawiyatan more emphasis on character concepts taught Ki Hajar Dewantara. Perception is based on the ideology that is applied at each school. The success of character education in schools can be seen from the actualization (practice) students in the form of attitude or action that looks at students. Actualization that appears on the high school student in Taman Madya Pawiyatan mother is covering tolerance, religious, discipline, honesty, creative, cooperative, communicative, caring, independent, patriotism and responsibility.